Lead-acid battery separator and lead-acid battery

The lead-storage battery separator with a conductive layer of continuous and dispersed phases addresses the issues of increased resistance and liquid loss by enhancing charging acceptance and cycle life through the use of low-potential metal compounds, specifically zinc oxide, to improve battery performance under partial state of charge conditions.

JP7624503B2Active Publication Date: 2025-01-30ASAHI KASEI KOGYO KABUSHIKI KAISHA
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
JP2023505556
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-08-31
Filing Date
2022-03-07
Publication Date
2025-01-30
Estimated Expiration
2042-03-07

AI Technical Summary

Technical Problem

Lead-storage batteries face issues with increased internal resistance, reduced charging acceptance, and liquid loss due to the formation of high crystalline sulfate on the electrode surface during partial state of charge (PSOC), leading to decreased cycle life and water decomposition.

Method used

A lead-storage battery separator with a conductive layer containing a continuous phase of conductive materials and a dispersed phase of low-potential metal compounds, such as zinc oxide, is used to enhance charging acceptance and reduce liquid loss by suppressing sulfation and water decomposition.

Benefits of technology

The separator improves charging performance, reduces liquid loss, and maintains battery integrity by preventing the peeling of the conductive layer, thus extending the battery's cycle life and maintaining efficient operation under PSOC conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007624503000002
    Figure 0007624503000002
  • Figure 0007624503000003
    Figure 0007624503000003
  • Figure 0007624503000001
    Figure 0007624503000001
Patent Text Reader

Abstract

The present invention provides: a separator for lead acid storage batteries, the separator exhibiting excellent charge acceptance performance and excellent liquid loss characteristics when in use under PSoC, while being not susceptible to the occurrence of ply separation within a lead acid storage battery and having good ER; and a lead acid storage battery which uses this separator for lead acid storage batteries. The present invention provides a separator for lead acid storage batteries, the separator comprising a base material and a conductive layer that is superposed on at least one surface of the base material. The conductive layer comprises: a continuous phase that is formed of a conductive material; and dispersed phases in the continuous phase, the dispersed phases being formed of at least one low-potential metal material that is selected from the group consisting of metals having a standard electrode potential of -0.7 V or less, metal compounds containing these metals, and combinations of these metals and metal compounds.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a separator for a lead-acid battery and a lead-acid battery using the same. [Background technology]

[0002] Lead-acid batteries are widely used worldwide in in-vehicle applications such as passenger cars, buses, trucks, motorcycles, and golf carts, as well as industrial applications such as forklifts, farm machinery, railways, UPS, and communication devices, etc. In particular, in recent in-vehicle applications, there is a demand for performance that allows operation at a partial state of charge (PSoC) of approximately 50% to 80%, such as in hybrid electric vehicles (HEVs) and idling start-stop (ISS) vehicles.

[0003] The main performance requirements for lead-acid batteries are charge acceptance, cycle characteristics, and water loss characteristics. Lead-acid batteries equipped with charge control functions and regenerative charging functions for environmental performance and fuel efficiency improvement have limited opportunities to charge. Therefore, charge acceptance is required to efficiently charge a large amount of energy into the battery. If a battery is maintained in PSoC for a long time, the cycle characteristics are likely to decrease. The reason is that in PSoC batteries, highly crystalline sulfates are easily formed on the electrode surface, and when the formed sulfate crystals accumulate, the charge acceptance performance of the electrode is dramatically reduced (sulfation), and finally the battery reaches its end of life. In addition, when the negative electrode reaches the hydrogen generation potential, water is decomposed and water loss occurs. Therefore, from the viewpoint of maintainability, improvement and maintenance of the water loss characteristics are required.

[0004] Lead-acid battery separators are generally membranes with a microporous structure that have voltage resistance characteristics, and are placed in close contact with the surfaces of both electrodes to prevent short circuits between the positive and negative electrodes. It is expected that the performance of batteries can be improved by improving the separator structure and controlling the electrode surface reaction that occurs at the contact surface between the separator and the electrode.

[0005] Conventionally, a structure (also simply referred to as a "layer" or "coating layer") has been provided on the surface of a base material of a separator for a lead-acid battery in order to promote electrode surface reactions by functioning as an auxiliary conductive path for the electrode in the separator surface (x-axis / y-axis plane) direction, thereby improving charge acceptance and cycle characteristics, etc. However, the above structure increases the electrical resistance (hereinafter also referred to as "ER") of the separator in the electrolyte, which increases the internal resistance of the battery and causes a decrease in the initial discharge capacity of the lead-acid battery.

[0006] Patent Document 1 discloses a technology for reducing float current, reducing water loss in lead-acid batteries, and improving cycle life by using a battery separator coated with or containing zinc salt.

[0007] Patent Document 2 discloses a technology for improving the charge acceptance and cycle life of a lead-acid battery by using a battery separator to which an engineered carbon material is applied or added.

[0008] Patent Document 3 discloses a technology for improving the charge acceptance of lead-acid batteries, improving surface conductivity, and reducing acid layering by using a battery separator containing zinc oxide as a filler. [Prior art documents] [Patent documents]

[0009] [Patent Document 1] International Publication No. 2017 / 143212 [Patent Document 2] International Publication No. 2015 / 171595 [Patent Document 3] International Publication No. 2017 / 062461 Summary of the Invention [Problem to be solved by the invention]

[0010] Patent Documents 1 and 3 do not describe the charge acceptance performance after a certain number of cycles, the water loss performance during use of the battery under PSoC (during cycles), and how to improve the ER. Patent Document 2 does not describe the water loss performance during use of the battery under PSoC (during cycles), and how to improve the ER.

[0011] An object of the present disclosure is to provide a separator for a lead-acid battery, which has excellent charge acceptance performance, excellent electrolyte loss characteristics during use under PSoC, and is less susceptible to layer peeling within the lead-acid battery and has a good ER, and a lead-acid battery using the separator. [Means for solving the problem]

[0012] Examples of embodiments of the present disclosure are listed below. [1] A separator for a lead-acid battery, comprising a substrate and a conductive layer laminated on at least one surface of the substrate, The conductive layer includes a continuous phase formed of a conductive material, and a dispersed phase in the continuous phase, the dispersed phase being formed of at least one low potential metal material selected from the group consisting of metals having a standard electrode potential of -0.7 V or less, metal compounds containing the metals, and combinations thereof. [2] 2. The separator for a lead-acid battery according to item 1, wherein, in a cross-sectional view of the conductive layer in the MD-ND cross section, a ratio of an area of ​​the dispersed phase to an area of ​​the continuous phase is 1% or more and 60% or less. [3] 3. The separator for a lead-acid battery according to item 1 or 2, wherein the low potential metal material comprises zinc or a zinc compound. [4] 4. The separator for a lead-acid battery according to any one of items 1 to 3, wherein the conductive material comprises a carbon material. [5] 5. The separator for a lead-acid battery according to any one of items 1 to 4, wherein an average value of the nearest interphase distance in a MD-ND cross section of the conductive layer is 0.1 μm to 2 μm. [6] 6. The lead-acid battery separator according to any one of items 1 to 5, wherein the low potential metal material has a maximum diameter of 0.1 μm to 15 μm. [7] 7. The lead-acid battery separator according to any one of items 1 to 6, wherein the amount of the low potential metallic material is 5% by mass to 60% by mass based on the total mass of the conductive layer. [8] 8. The lead-acid battery separator according to any one of items 1 to 7, wherein the low potential metal material is at least one selected from the group consisting of zinc oxide and zinc sulfate. [9] 9. The lead-acid battery separator according to any one of items 1 to 8, wherein the carbon material is at least one selected from the group consisting of furnace black, acetylene black, ketjen black, and carbon nanotubes.

[10] A lead-acid battery comprising: a positive electrode; a negative electrode; and the separator according to any one of items 1 to 9 between the positive electrode and the negative electrode.

[11] A lead-acid battery comprising a positive electrode, a negative electrode, a separator between the positive electrode and the negative electrode, and an electrolyte, The separator is A substrate and a conductive layer laminated on at least one surface of the substrate, the conductive layer comprises a conductive material, and holes are present in the conductive layer; a ratio of an area of ​​the holes to an area of ​​the conductive layer in a MD-ND cross section of the conductive layer is 1% or more and 60% or less; The electrolyte of the lead-acid battery contains at least one low-potential metal material selected from the group consisting of metals having a standard electrode potential of -0.7 V or less, metal compounds containing the metals, and combinations thereof.

[12] Item 12. The lead-acid battery according to item 11, wherein the low potential metallic material is zinc or a zinc compound.

[13] Item 13. The lead-acid battery according to item 11 or 12, wherein the conductive material comprises a carbon material. Effect of the Invention

[0013] According to the present disclosure, it is possible to provide a separator for a lead-acid battery, which has excellent charge acceptance performance, excellent electrolyte loss characteristics when used under PSoC, and is less susceptible to layer peeling within the lead-acid battery and has a good ER, and a lead-acid battery using the separator. [Brief description of the drawings]

[0014] [Figure 1] 2 is an example of a cross-sectional image of a lead-acid battery separator having a conductive layer of Example 1, taken by SEM. [Diagram 2] FIG. 2 is a conceptual diagram showing a method for measuring the average value of the nearest dispersed phase distance. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] <Lead-acid battery separator> The separator for a lead-acid battery (hereinafter, also simply referred to as "separator") of the present disclosure has a substrate and a conductive layer laminated on at least one side of the substrate. The conductive layer includes a continuous phase formed of a conductive material, and a dispersed phase in the continuous phase, the dispersed phase being formed of at least one material selected from the group consisting of a metal having a standard electrode potential of -0.7 V or less, a metal compound containing the metal having a standard electrode potential of -0.7 V or less, and a combination thereof (hereinafter, also simply referred to as "low potential metal material" in the present specification). The separator is disposed between a positive electrode and a negative electrode, and prevents an electrical short circuit between the positive electrode and the negative electrode. The conductive layer may be laminated on both sides of the substrate, and may be laminated entirely or partially on one or both sides of the substrate. In the present specification, when the conductive layer is "laminated" on one or both sides of the substrate, it includes a case where the conductive layer is directly laminated on the substrate and a case where the conductive layer is indirectly laminated via another layer.

[0016] The lead-acid battery separator of the present disclosure has excellent charge acceptance performance, excellent electrolyte loss characteristics when used under PSoC, and good ER with little peeling of layers in the lead-acid battery. The reason is presumed to be as follows, without being limited by theory. That is, in the past, a structure (simply called a "surface layer") has been provided on the surface of the base material of the lead-acid battery separator in the separator surface (x-axis / y-axis plane) direction in order to promote the electrode surface reaction by functioning as an auxiliary conductive path of the electrode, thereby improving the charge acceptance and cycle characteristics. Examples of materials for the surface layer include inorganic substances, organic substances, and mixtures of organic substances and inorganic substances. In addition, in the past, metals or metal compounds have been added to the surface layer in order to suppress deterioration of electrolyte loss characteristics. However, there was a problem that the ER increases due to the above structure, which increases the internal resistance of the battery and causes a decrease in the initial discharge capacity of the lead-acid battery. In response to this, the inventors have designed the surface layer to contain a conductive material and a metal having a standard electrode potential of -0.7V or less, or a metal compound containing the metal having a standard electrode potential of -0.7V or less, and to have the conductive material of the surface layer form a continuous phase and the metal or metal compound form a dispersed phase, thereby partially restricting the formation of a conductive path on the separator surface, thereby reducing the water decomposition reaction and suppressing the deterioration of the liquid loss characteristics. In addition, since sulfation is suppressed by the conductive path on the separator surface, the charge acceptance performance can be improved. In addition, since the phase formed by the conductive material is a continuous phase, layer peeling is unlikely to occur. And, since the conductive layer has holes, the ER is good. It is believed that this has made it possible to provide a lead-acid battery separator that has excellent charge acceptance performance, excellent liquid loss characteristics when used under PSoC, and has good ER with little layer peeling in the lead-acid battery.

[0017] Conductive Layer The conductive layer includes a continuous phase and a dispersed phase in the continuous phase. In order to improve the conductivity of the continuous layer, the ratio of the area of ​​the dispersed phase to the area of ​​the continuous phase is preferably 1% to 60%, more preferably 1% to 55%, and even more preferably 1% to 50%, in a cross-sectional view of the MD-ND cross section of the conductive layer.

[0018] From the viewpoint of preventing peeling or falling off of the conductive layer from the separator and forming a uniform conductive layer on the substrate surface, the thickness of the conductive layer is preferably 0.1 μm to 30 μm, more preferably 0.1 μm to 25 μm, even more preferably 0.1 μm to 20 μm, and even more preferably 0.1 μm to 15 μm.

[0019] Conductive Materials The continuous phase is formed of a conductive material. The continuous phase may contain a material other than the conductive material as long as the conductive path of the conductive material is not lost. The conductive material preferably contains a carbon material from the viewpoint of conductivity. Examples of the carbon material include carbon clusters such as graphite, activated carbon, carbon black, graphene, and fullerene, carbon monolithic materials, and mixtures thereof. Among the above carbon materials, from the viewpoint of conductivity, furnace black, acetylene black, ketjen black, graphite, and carbon nanotubes are more preferable, and furnace black, acetylene black, ketjen black, and carbon nanotubes are even more preferable.

[0020] The median particle size (d50) of the conductive material, preferably the carbon material, is preferably 0.01 μm to 50 μm, more preferably 0.01 μm to 30 μm, and even more preferably 0.01 μm to 10 μm, from the viewpoint of facilitating the formation of a layer with a uniform thickness.

[0021] <Low potential metal materials> The dispersed phase is formed of a low-potential metal material selected from the group consisting of a metal having a standard electrode potential of -0.7V or less, a metal compound containing a metal having a standard electrode potential of -0.7V or less as a constituent element, and a combination thereof. The dispersed phase is preferably made of a low-potential metal material. The conductive layer has the dispersed phase, which partially restricts the formation of a conductive path on the separator surface, thereby reducing the water decomposition reaction and suppressing the deterioration of the liquid reduction characteristic. The form of the low-potential metal material is not limited, but is preferably in the form of particles. The phase in the dispersed phase may be formed of a single particle of the low-potential metal material, or may be formed by agglomeration of multiple particles. The standard electrode potential is the electrode potential when the activity of all substances involved in a certain electrochemical reaction is 1 and in equilibrium, and is expressed with the potential of the standard hydrogen electrode as 0V. The low-potential metal material preferably does not contain a metal having a standard electrode potential of more than -0.7V and / or a metal compound containing a metal having a standard electrode potential of more than -0.7V as a constituent element so as not to affect the battery performance.

[0022] Examples of metals having a standard electrode potential of -0.7 V or less include zinc, vanadium, chromium, manganese, zirconium, titanium, aluminum, beryllium, magnesium, sodium, calcium, strontium, barium, potassium, rubidium, lithium, etc. Examples of metal compounds containing a metal having a standard electrode potential of -0.7 V or less as a constituent element include hydrides, oxides, hydroxides, halides, nitrides, oxoacid salts, sulfates, nitrates, carbonates, acetates, metal complexes (coordination compounds), organometallic compounds, etc.

[0023] From the viewpoint of suppressing deterioration of the liquid reduction characteristic, the low potential metal material preferably contains zinc or a zinc compound. For example, zinc, zinc oxide, zinc sulfate, zinc fluoride, zinc chloride, zinc bromide, zinc iodide, zinc sulfide, zinc nitrate, zinc trifluoromethanesulfonate, zinc phosphide, zinc phosphate, zinc diphosphate, zinc borate, zinc propionate, zinc arsenate, zinc carbonate, zinc thiocyanate, zinc pyrophosphate, zinc peroxide, zinc perchlorate, zinc acetate, zinc diethoxy, zinc 2-ethylhexanoate, zinc laurate, zinc stearate, zinc naphthenate, zinc acetylacetonate, zinc myristate, zinc palmitate, zinc ricinoleate, zinc undecylenate, zinc aspartate, zinc acetylmethionine, zinc gluconate, zinc citrate, zinc polypyrrolidone carboxylate, zinc picolinate, etc. may be mentioned. Among the above zinc or zinc compounds, in order to suppress deterioration of the liquid reducing properties, zinc, zinc oxide and zinc sulfate are more preferred, zinc oxide or zinc sulfate are even more preferred, and zinc oxide is even more preferred.

[0024] From the viewpoint of suppressing deterioration of the liquid reduction characteristic, the maximum diameter of the low potential metal material is preferably 15 μm or less, more preferably 10 μm or less, and even more preferably 7 μm or less. The lower limit of the maximum diameter that can be combined with these upper limits is not particularly limited, but may be, for example, 0.1 μm or more. From the viewpoint of suppressing deterioration of the liquid reduction characteristic, the average distance between the closest dispersed phases (also referred to as the "closest dispersed phase distance" in the present disclosure) in the cross-sectional view in the MD-ND cross section of the conductive layer is preferably 0.2 μm to 2 μm, more preferably 0.2 μm to 1 μm, and even more preferably 0.3 μm to 0.6 μm.

[0025] The amount of the low potential metal material in the conductive layer is preferably 60 mass % or less based on the mass of the entire conductive layer from the viewpoint of suppressing peeling of the layer. The amount of the low potential metal material in the conductive layer is preferably 5 mass % or more based on the mass of the entire conductive layer from the viewpoint of liquid reduction characteristics. The amount of the low potential metal material in the conductive layer is more preferably 10 mass % to 50 mass %, and even more preferably 20 mass % to 40 mass %.

[0026] The median particle size (d50) of the low potential metallic material is preferably 0.01 μm to 50 μm, more preferably 0.01 μm to 30 μm, and even more preferably 0.01 μm to 20 μm, from the viewpoint of suppressing peeling of the conductive layer.

[0027] <Surfactants> The conductive layer may contain a surfactant from the viewpoint of uniformly dispersing the conductive material of the conductive layer. The surfactant may be present in both the continuous phase and the dispersed phase. When the material of the conductive layer is a carbon material, the surfactant is more preferable because the surfactant allows the carbon material to be uniformly distributed throughout the conductive layer and form a uniform conductive path. As the surfactant, various surfactants can be used, such as anionic surfactants such as sulfate ester type, phosphate ester type, carboxylic acid type, and sulfonic acid type, cationic surfactants such as quaternary ammonium salt type and amidoamine type, amphoteric surfactants such as alkyl betaine type, amido betaine type, and amine oxide type, nonionic surfactants such as ether type, fatty acid ester type, and alkyl glucoxide, and polymer surfactants such as polyacrylic acid, polyacrylic acid salts, polysulfonate salts, polynaphthalene sulfonate salts, polyalkylene polyamine alkylene oxide, polyalkylene polyimine alkylene oxide, polyvinyl picridene, and cellulose type. In order to prevent the fillers from agglomerating, these can be used alone or in combination of two or more types. As long as the effect of uniformly dispersing the conductive material of the conductive layer can be obtained, the surfactant is not limited to these. The surfactant preferably includes at least one selected from the group consisting of ionic surfactants, i.e., anionic surfactants, cationic surfactants, and amphoteric surfactants.

[0028] The amount of the surfactant is preferably 1 part by mass to 100 parts by mass, and more preferably 10 parts by mass to 60 parts by mass, based on 100 parts by mass of the total conductive material in the conductive layer.

[0029] <resin> The conductive layer preferably contains a resin from the viewpoints of increasing the binding strength of the conductive material and suppressing peeling or falling off of the conductive layer from the substrate. The resin may be present in both the continuous phase and the dispersed phase. Examples of the resin include styrene resin, acrylic-urethane resin, acrylic-styrene resin, vinyl acetate-acrylic resin, styrene-butadiene resin, acrylonitrile-butadiene resin, natural rubber resin, polybutadiene resin (BR resin), methyl methacrylate-butadiene resin, 2-vinylpyridine-styrene-butadiene resin (VP resin), chloroprene resin (CR resin), polyolefin resin such as polyethylene, polypropylene, polybutene, or copolymers thereof, modified polyolefin resin obtained by chlorinating or acid-modifying the polyolefin resin, fluorine-containing resin such as polyvinylidene fluoride or polytetrafluoroethylene, fluorine-containing rubber binder such as vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene copolymer or ethylene-tetrafluoroethylene copolymer, (meth)acrylic acid-styrene-butadiene copolymer resin and its hydrogenated product, polyvinyl alcohol resin, and polyvinyl alcohol-polyacetate copolymer resin.

[0030] Among the above resins, from the viewpoint of improving the binding property and heat resistance, acrylic resin or styrene resin is more preferable, and acrylic resin is further preferable. In this specification, "acrylic resin" includes acrylic copolymer resins such as acrylic-urethane resins, acrylic-styrene resins, acrylic-styrene-butadiene resins, and vinyl acetate-acrylic resins, as well as polymers such as acrylic resins. In this specification, "styrene resin" includes styrene copolymer resins such as acrylic-styrene resins, styrene-butadiene resins, acrylic-styrene-butadiene resins, and 2-vinylpyridine-styrene-butadiene resins, as well as polymers such as styrene resins.

[0031] The amount of the resin is preferably 1 part by mass to 100 parts by mass, and more preferably 10 parts by mass to 40 parts by mass, based on 100 parts by mass of the total conductive material of the conductive layer.

[0032] These resins may contain one or more other components in the composition exemplified above. The resin is not limited to one type, and multiple types can be used in combination. For example, a combination of an acrylic resin and a styrene resin can be exemplified.

[0033] <Thickener> The conductive layer preferably contains a thickener from the viewpoint of suppressing peeling or falling off of the conductive layer from the substrate and forming a uniform conductive layer on the substrate surface. The thickener may be present in both the continuous phase and the dispersed phase. Examples of the thickener include synthetic polymers such as polyethylene glycol, polypropylene glycol, urethane-modified polyether, polyacrylic acid, polyvinyl alcohol, and vinyl methyl ether-maleic anhydride copolymer, cellulose derivatives such as carboxymethyl cellulose (CMC), carbomethoxycellulose, hydroxyethyl cellulose, and hydroxypropyl cellulose, natural polysaccharides such as xanthan gum, diutan gum, welan gum, gellan gum, guar gum, carrageenan gum, and pectin, and starches such as dextrin and pregelatinized starch. The thickener is appropriately selected from the viewpoints of the viscosity, pot life, and particle size distribution of the slurry. These may be used alone or in combination of two or more.

[0034] The amount of the thickener is preferably 0.1 to 50 parts by mass, and more preferably 1 to 20 parts by mass, relative to 100 parts by mass of the total conductive material in the conductive layer.

[0035] <hole> The conductive layer preferably has holes from the viewpoint of improving ER. The conductive layer is typically porous. The maximum pore size of the pores is 15 μm or less, preferably 10 μm or less, more preferably 7 μm or less, in cross-sectional view in the MD-ND cross section of the conductive layer. The lower limit of the maximum pore size that can be combined with these upper limits is not particularly limited, but may be, for example, 0.1 μm or more, in cross-sectional view in the MD-ND cross section of the conductive layer.

[0036] From the viewpoint of improving ER, the ratio of the area of ​​the holes to the area of ​​the conductive layer is preferably 1% or more and 60% or less in cross section in the MD-ND cross section of the conductive layer, more preferably 1% or more and 55% or less, and even more preferably 1% or more and 50% or less.

[0037] <Base material> The substrate is not particularly limited as long as it is microporous so that ions can pass through it, and preferably includes porous membranes made from natural or synthetic materials such as thermoplastic polymers such as polyvinyl and polyolefin, thermosetting polymers such as phenolic resin, rubber materials such as natural or synthetic rubber and latex, fibrous materials such as synthetic wood pulp (SWP), glass fiber, synthetic fiber, and cellulose fiber, and combinations thereof, and more preferably, microporous membranes made from thermoplastic polymers. Thermoplastic polymers basically include any acid-resistant thermoplastic material suitable for use in lead-acid batteries, and preferred thermoplastic polymers include, for example, polyvinyl and polyolefin. Polyvinyl includes, for example, polyvinyl chloride (PVC). Polyolefin includes, for example, polyethylene and polypropylene. Polyethylene includes, for example, ultra-high molecular weight polyethylene (UHMWPE).

[0038] 《Lead acid battery》 The lead-acid battery of the present disclosure includes the separator for the lead-acid battery of the present disclosure. The lead-acid battery includes a positive electrode, a negative electrode, and a separator of the present disclosure disposed between the positive electrode and the negative electrode. The lead-acid battery further includes an electrolyte. The electrolyte preferably includes at least one low-potential metal material selected from the group consisting of a metal having a standard electrode potential of -0.7 V or less, a metal compound containing a metal having a standard electrode potential of -0.7 V or less, and a combination thereof. The lead-acid battery of the present disclosure has a ratio of the area of ​​the holes to the area of ​​the conductive layer of 1% to 60% and includes a low-potential metal material in the electrolyte, and thus has excellent charge acceptance performance, excellent liquid loss characteristics when used under PSoC, and good ER with less peeling of layers in the lead-acid battery. The reason for this is not limited to theory, but is presumed to be as follows. That is, sulfation is suppressed by the conductive path on the surface of the separator, and thus charge acceptance performance can be improved. In addition, the low-potential metal material in the electrolyte reduces the decomposition reaction of water and suppresses deterioration of the liquid loss characteristics. In addition, because the phase formed of the conductive material is a continuous phase, peeling of the layers is unlikely to occur, and because the conductive layer has pores, the ER is good.

[0039] The electrolyte may contain dilute sulfuric acid. The positive electrode grid constituting the positive electrode may be lead or a lead alloy, and the positive electrode active material may be lead oxide, for example, lead dioxide. The negative electrode grid constituting the negative electrode may be lead or a lead alloy, and the negative electrode active material may be lead, and the lead negative electrode itself may be, for example, in a spongy form. The active materials of these positive and negative electrodes may contain 50 mass % or less of other metal elements other than lead or lead alloy. The dilute sulfuric acid is sulfuric acid with a specific gravity of 1.1 to 1.4, and the electrolyte may contain an additive. The additive may contain, for example, aluminum ions from the viewpoint of suppressing sulfation. Other additives include metal ions such as lithium ions and sodium ions.

[0040] By providing the separator of the present disclosure between the positive electrode and the negative electrode, a lead-acid battery having excellent charge acceptance performance, excellent electrolyte loss characteristics during use under PSoC, and excellent ER with less peeling of layers in the lead-acid battery can be obtained. From the viewpoint of improving the charge acceptance of the negative electrode, it is preferable that the separator has a conductive layer on the negative electrode side. The separator for lead-acid batteries of the present disclosure can be used in both open-type lead-acid batteries and valve-regulated lead-acid batteries.

[0041] <<Manufacturing method for lead-acid battery separator>> <Preparation of substrate> Hereinafter, the manufacturing method will be described using an example of a substrate made of polyolefin, for example, ultra-high molecular weight polyethylene. However, the substrate is not limited to substrates obtained by the manufacturing method described below, as long as the conductive layer of the present disclosure can be formed thereon.

[0042] The method for producing the substrate includes the steps of: preparing a thermoplastic polymer, such as ultra-high molecular weight polyethylene (hereinafter referred to as "UHMWPE"); preparing a particulate filler; preparing a processing plasticizer that is liquid at room temperature (25°C); mixing the UHMWPE, the particulate filler, and the processing plasticizer to form a mixture; extruding the mixture through a die, such as a slot die or a blown film die, to form a sheet; and extracting the sheet to partially or completely remove the plasticizer from the sheet, thereby forming a microporous matrix. After forming the sheet, and before the extracting step, the sheet may be further processed by casting on a chilled roller, calendering, or blown film. The cast or calendered sheet may then be subjected to the extracting step to partially or completely remove the plasticizer, thereby forming a microporous matrix.

[0043] The microporous matrix obtained by the above method includes UHMWPE, plasticizer (if partially extracted), and particulate filler dispersed throughout the matrix. The particulate filler preferably accounts for 5 to 95 percent by weight of the microporous matrix. In the present specification, the term "microporous matrix" refers to a structure having a network of interconnected pores, the entire microporous matrix being connected by the above-mentioned constituent materials. The pores preferably account for 25 to 90 percent of the volume of the microporous matrix. The method for producing a substrate may further include, after the extraction step, a step of stretching the microporous matrix; and a step of calendering the stretched microporous matrix to produce a final microporous material. By carrying out the above-mentioned calendering, a substrate having excellent dimensional stability even at high temperatures can be formed.

[0044] <Formation of Conductive Layer> The conductive layer may be directly laminated on the surface of the substrate, or may be indirectly laminated as a laminate conductive layer of a substrate having a laminate consisting of a single layer or multiple layers. In the latter case, the conductive layer may be introduced as the final step of a process of laminating a single layer or multiple layers onto the substrate, or the conductive layer may be introduced into a part of the laminate material, and then the substrate and the laminate including the conductive layer may be superimposed and introduced.

[0045] The method for forming the conductive layer to be laminated on the substrate includes the steps of: mixing the materials forming the conductive layer with a solvent; introducing the mixture of materials onto the surface of the substrate or laminate; and drying the mixture to remove the solvent. The materials are preferably homogenized in the solvent to form a mixture. The solvent may be an aqueous solvent or an organic solvent. The introduction method may include applying the mixture in a wet state to the surface of the substrate or laminate, for example, by die coating or gravure coating. The substrate or laminate to which the mixture has been applied may be further processed, such as by pressing.

[0046] From the viewpoint of easily forming a conductive layer having uniform low surface electrical resistance, it is more preferable that in the drying step, the wet mixture introduced onto the surface of the substrate or laminate is gently dried at a constant speed in an atmosphere of 80° C. An example of the drying method is hot air drying. By evaporating the solvent at a constant speed, the mixture remains as a layer without uneven distribution of solids, forming a conductive layer with a uniform structure.

[0047] In order to adjust the average value of the nearest dispersed phase distance in the conductive layer to 0.2 μm to 2 μm, it is preferable to add low-potential metal material particles in the process of mixing the material forming the conductive layer and the solvent from the viewpoint of reducing the number of steps. At this time, in order to adjust the nearest dispersed phase distance, the low-potential metal material particles may be pulverized using a pulverizer or the like. For example, a slurry containing low-potential metal material particles, a dispersant, and water may be bead milled to obtain a good dispersed state without agglomerating the low-potential metal material particles. The average median particle size D50 of the low-potential metal material particles may be adjusted to be preferably 20 μm or less. In addition, in order to adjust the nearest dispersed phase distance, the amount of low-potential metal material particles to be added may be adjusted to be 60 mass % or less based on the total mass of the conductive layer to be formed, thereby preventing agglomeration and obtaining a good dispersed state.

[0048] <<Manufacturing method of lead-acid battery>> The lead-acid battery of the present disclosure can be manufactured, for example, by disposing the separator of the present disclosure between a positive electrode and a negative electrode, placing the separator in a battery container, and injecting an electrolyte. The form of the separator for the lead-acid battery can be determined so as to be compatible with each component of the lead-acid battery. Although not particularly limited, it is preferable that the separator has the above layer disposed on the negative electrode side from the viewpoint of improving the charge acceptance of the negative electrode. The separator for the lead-acid battery of the present disclosure can be used in both an open-type lead-acid battery and a valve-regulated lead-acid battery. EXAMPLES

[0049] <<Maximum pore size and pore area ratio of conductive layer>> The maximum pore size of the conductive layer was determined by the following method. A laminate in which one lead oxide positive electrode, one lead negative electrode, and one separator to be measured were stacked in the order of positive electrode-separator-negative electrode was placed in a polycarbonate battery container. Dilute sulfuric acid with a specific gravity of 1.28 was poured into the battery container as an electrolyte to prepare a lead-acid battery (2V single cell), which was then left to stand at 25°C for 24 hours. The separator was then removed, washed with water, and dried.

[0050] From the dried separator, a 5 cm square was cut out from a portion where the laminate was uniformly present without any chipping, abrasion, or color unevenness of the conductive layer. In order to remove the additives from the separator, the separator was washed with ethanol (total immersion time about 4 hours, ethanol was replaced three times), and then air-dried. Then, a smooth cross section was prepared by processing the cross section using an ion milling device. The ion milling device was SM-09010 (manufactured by JEOL Ltd.) and performed at an acceleration voltage of 3.5 kV to prepare the MD-ND cross section (cross section parallel to MD) of the separator. Then, the above cross section sample was fixed to a SEM sample stage for cross section observation with a conductive adhesive (carbon-based), dried, and then osmium coating was performed as a conductive treatment using an osmium coater (HPC-30W, manufactured by Vacuum Device Co., Ltd.) under the conditions of an applied voltage adjustment knob setting of 4.5 and a discharge time of 3 seconds, and a microscopic specimen was prepared. The MD-ND cross section was observed using an SU8220 (manufactured by Hitachi High-Tech Corporation) under SEM observation. The observation conditions were an accelerating voltage of 1 kV, use of an Upper detector (LA100), working distance of 5 mm, observation magnification of 10,000 times, and image pixel count of 1280 x 960. The observation field of view was determined so that the entire thickness direction of the carbon coating layer was included, and after focusing and astigmatism correction, the brightness and contrast were set so that the holes could be clearly observed without saturating the brightness value, and images were taken. The SEM images obtained under the above conditions were subjected to hole analysis using free software ImageJ to determine the maximum hole diameter. The image range analyzed was the area of ​​the obtained SEM images that included only the conductive layer and had an area of ​​10 μm 2 Two sides were selected so that the above was the case.

[0051] The analysis procedure is as follows. First, the relevant carbon coating layer area was cut out and a median filter (radius: 4) was applied to remove noise. Then, Otsu was selected as the threshold condition for image binarization, and the image was binarized. Dilate processing was performed once on the holes in this binary image. After that, the area (nm2) of each hole was calculated using Analyze Particles. 2 ) was calculated to obtain the maximum pore diameter. Holes on the edges of the image were also included in the analysis. The maximum pore diameter is the equivalent circle diameter (the diameter of a circle with the same area as the hole area) calculated from the maximum hole area. The formula for calculating the maximum pore diameter is as follows: Maximum pore size = 2 × (maximum pore area / π) 0.5

[0052] The ratio of the area of ​​the hole to the area of ​​the conductive layer is calculated by the area (nm 2 ) versus the sum of the areas of each hole (nm 2 ) and is as follows: Ratio of the area of ​​the holes to the area of ​​the conductive layer = {total area of ​​each hole (nm 2 ) / Area of ​​the analyzed image (nm 2 )}×100

[0053] <Maximum diameter of low-potential metal material> The maximum diameter of the low-potential metal material was determined by the following method. From the prepared separator, a 5 cm square was cut out from a portion where the laminate was uniformly present without any chipping, abrasion, or color unevenness of the conductive layer, as visually observed. In order to remove the additives from the separator, the separator was washed with ethanol (total immersion time was about 4 hours, and the ethanol was replaced three times), and then air-dried. Then, a cross-section was processed using an ion milling device to prepare a smooth cross-section. The ion milling device was SM-09010 (manufactured by JEOL Ltd.) and performed at an acceleration voltage of 3.5 kV to prepare an MD-ND cross-section (cross-section parallel to MD) of the separator. Then, the above cross-section sample was fixed to a SEM sample stage for cross-section observation with a conductive adhesive (carbon-based), dried, and then osmium coating was performed as a conductive treatment using an osmium coater (HPC-30W, manufactured by Vacuum Device Co., Ltd.) under the conditions of an applied voltage adjustment knob setting of 4.5 and a discharge time of 3 seconds, and used as a microscopic specimen. The MD-ND cross section was observed by SEM using SU8220 (Hitachi High-Tech Corporation). The observation conditions were accelerating voltage 1 kV, Upper detector (LA100) used, working distance 5 mm, observation magnification 10,000 times, and image pixel number 1280 × 960. The observation field was determined so that the entire thickness direction of the carbon coating layer was included, and after focusing and astigmatism correction, the brightness and contrast were set so that the particles could be clearly observed without saturating the brightness value, and the image was taken. Particle analysis of the low-potential metal material was performed on the SEM image obtained under the above conditions using free software ImageJ to determine the maximum diameter. The image range for particle analysis was the area of ​​the obtained SEM image that included only the conductive layer and had an area of ​​10 μm 2 Two sides were selected so that the above was the case.

[0054] The procedure for particle analysis is as follows. First, the relevant carbon coating layer area was cut out and a median filter (radius: 4) was applied to remove noise. Then, Otsu was selected as the threshold condition for image binarization, and the image was binarized. Dilate processing was performed once on the particles in this binary image. After that, the area (nm 2) was calculated to obtain the maximum diameter. Particles hanging on the edge of the image were also included in the analysis. The maximum diameter is the equivalent circle diameter (the diameter of a circle with the same area as the particle area) calculated from the area of ​​the largest particle. The formula for calculating the maximum diameter is as follows: Maximum diameter = 2 × (maximum particle area / π) 0.5

[0055] 《Average value of nearest neighbor interphase distance》 The average value of the nearest inter-dispersed phase distance was calculated based on the binary image obtained above using the dispersibility measurement function of the image analysis software "Azokun" manufactured by Asahi Kasei Corporation. FIG. 2 is a conceptual diagram showing the measurement method. As shown in FIG. 2, the "nearest inter-dispersed phase distance" is a distance (μm) calculated by, when focusing on one dispersed phase (2) in the continuous phase (1) in the image to be analyzed (10), specifying the other dispersed phase (2') closest to it, and subtracting the sum of the circle equivalent radius of each dispersed phase from the distance (4) between the centers of gravity of the pair of dispersed phases. Here, the distance between the centers of gravity is the length of a straight line connecting the centers of gravity (3) of the nearest dispersed phases. The above software determines the centers of gravity (3) of each dispersed phase present in dispersion, specifies the other dispersed phase closest to each dispersed phase, connects the centers of gravity of the nearest dispersed phases with straight lines in a network shape, and calculates the distance between the dispersed phases after determining the length of each straight line. The processing procedure is as follows. After loading the binary image into the software and setting the actual scale, select and execute "Wall distance" in the dispersity measurement of the analysis menu. During the analysis, the dispersed phase (5) that is in contact with the outer frame of the image is excluded from the analysis target by edge correction, and no additional filter processing is performed. This series of processing results in a list of the nearest dispersed phase distances (for example, in Figure 2, the four nearest dispersed phase distances (4)). The number average value (μm) of the nearest dispersed phase distances was obtained. The image area for calculating the nearest dispersed phase distances was the same as the image area for which the above particle analysis was performed.

[0056] <Area ratio of dispersed phase to continuous phase> The ratio of the area of ​​the dispersed phase to the continuous phase was calculated based on the binary image obtained above. The binary image was read into JupiterHub, and the ratio of the area of ​​the particle portion of the low-potential metal material was calculated. The image area used to calculate the ratio of the area of ​​the dispersed phase to the continuous phase was the same as the image area used for the particle analysis.

[0057] 《Center particle size (D50)》 The median particle size of the low-potential metal material was measured for a dispersion and mixture of the low-potential metal material and an ionic surfactant in water (hereinafter referred to as the "metal compound dispersion"). The median particle size was measured using a Microtrac-Bell MT3300EXII (optical bench) and SDC (data circulator). The measurement software used was MicrotracII. The measurement and analysis conditions were as follows: [Measurement conditions] SetZeroTime: 10 Measurement time: 10 Number of measurements: 1 [Analysis conditions] Transparency: Drop Particle Refractive Index: 2.00 Shape: Non-spherical Solvent Refractive Index: 1.333

[0058] <Unit water loss (liquid loss characteristics)> A lead-acid battery (2V single cell) was prepared using a polycarbonate battery case, two lead oxide positive electrodes, and one lead negative electrode, and was filled with dilute sulfuric acid with a specific gravity of 1.28 as an electrolyte. This lead-acid battery was used to carry out a charge-discharge cycle test of the lead-acid battery in a PSOC. For this test, an ACD-01 G-Version charge-discharge tester manufactured by Asuka Electronics was used. The specific conditions for the charge-discharge cycle test were as follows: at 25°C, the lead-acid battery was first discharged in a fully charged state, as shown in (1) below, and then (2) to (3) were counted as one cycle, and the cycle was stopped when the 510th cycle was completed. (1) Initial discharge: Current rate 0.2C (4×I20), constant current discharge for 150 minutes (2) Charging: Current rate 0.35C (7×I20), voltage value 2.4V, constant current-constant voltage charging for 40 minutes (3) Discharge: Current rate 0.35C (7 x I20), voltage value 1.75V, constant current-constant voltage discharge for 30 minutes Furthermore, the difference in weight of the lead-acid battery before the start of the cycles and after the completion of the 510th cycle was calculated as the amount of water loss. The amount of water loss was divided by the battery capacity of the lead-acid battery to calculate the unit water loss. The calculated unit water loss was evaluated according to the following criteria. A:1.39g / Ah / 510cycle or less B: More than 1.39g / Ah / 510cycle and less than 1.50g / Ah / 510cycle C: More than 1.50g / Ah / 510cycle

[0059] <Charging acceptance capacity (DCA)> DCA was measured by temporarily suspending the lead-acid battery during the cycle count measurement after the aforementioned charge-discharge cycle test was performed. Specifically, the cycle was stopped when the 510th cycle was completed, and charging and discharging were performed under the following conditions, and the charging current value was measured. (4) Charging (SoC 100%): Current rate 0.25C (5 x I20), voltage value 2.67V, constant current-constant voltage charging for 24 hours (5) Discharge (SoC 90%): Current rate 0.1C (2×I20), constant current discharge for 60 minutes (6) Charging: Current rate 2.0C (40×I20), voltage value 2.47V, constant current-constant voltage charging for 60 seconds (7) Discharge (SoC 80%): Current rate 0.1C (2×I20), constant current discharge for 60 minutes (8) Charging: Current rate 2.0C (40×I20), voltage value 2.47V, constant current-constant voltage charging for 60 seconds (9) Discharge (SoC70%): Current rate 0.1C (2×I20), constant current discharge for 60 minutes (10) Charging: Current rate 2.0C (40×I20), voltage value 2.47V, constant current-constant voltage charging for 60 seconds (11) Discharge (SoC60%): Current rate 0.1C (2×I20), constant current discharge for 60 minutes (12) Charging: Current rate 2.0C (40×I20), voltage value 2.47V, constant current-constant voltage charging for 60 seconds In the charging in (10) above, the current value at 60 seconds was recorded, and the current value was divided by the electrode capacity to obtain DCA. The obtained DCA was evaluated according to the following criteria. A: 0.70A / Ah or more B: 0.60A / Ah or more and less than 0.70A / Ah C: If it is less than 0.60A / Ah, it is C

[0060] Electrical resistance in electrolyte (ER) The ER was measured using a Caltronics Palico measurement system, with dilute sulfuric acid with a specific gravity of 1.28 used for the sulfuric acid bath, which was set at 27°C. First, the ER of the separator in a dry state was measured at three points, and the average value was calculated as the electrical resistance (ER) in the dry state. Prior to measurement, the separator was immersed in dilute sulfuric acid with a specific gravity of 1.28 and a temperature of 25°C for 24 hours. Under the above measurement conditions, the ER of the separator immersed in dilute sulfuric acid was measured at three points, and the average value was calculated as the electrical resistance (ER) in the electrolyte. The unit is Ω cm. 2 The obtained ER was evaluated according to the following criteria: A: ER in the electrolyte is 1.10 times or less than the ER in the dry state B: ER in the electrolyte is more than 1.10 times and less than 1.20 times the ER in the dry state C: ER in electrolyte is more than 1.20 times that of dry state.

[0061] Peeling Off Layers The peeling of the layers was checked by visually inspecting the bottom of the cell 24 hours after the 2V single cell was produced. If black powder was found on the bottom, it was determined that peeling of the layers had occurred, and this was recorded in Table 1.

[0062] Example 1 A polyethylene separator (RipTide C manufactured by Daramic) was used as the substrate. Metal or metal compound, carbon black, ionic surfactant, acrylic copolymer latex and thickener were dispersed and mixed as solid contents to prepare a slurry for forming a conductive layer. First, 20% by mass of zinc oxide (manufactured by Sakai Chemical Industry Co., Ltd. 1) based on the total mass of the solid contents in the slurry as the metal or metal compound, and 6.0% by mass of Lion Specialty Chemicals as the ionic surfactant based on the total mass of the solid contents in the slurry were mixed in water, and the mixture was crushed and dispersed using a grinder so that the median particle size D50 was 20 μm or less, to obtain a zinc compound dispersion. Next, the zinc compound dispersion was dispersed and mixed with 45.8% by mass of carbon black manufactured by Cabot Corporation based on the total mass of the solid contents in the slurry, 13.7% by mass of an ionic surfactant manufactured by Lion Specialty Chemicals Corporation based on the total mass of the solid contents in the slurry, 13.2% by mass of an acrylic copolymer latex manufactured by Asahi Kasei Corporation based on the total mass of the solid contents in the slurry, and 1.3% by mass of carboxymethylcellulose (CMC) as a thickener based on the total mass of the solid contents in the slurry to prepare a slurry.

[0063] The slurry was manually applied (hand-coated) to the back web surface of the substrate using an applicator, and dried in an oven at 80°C for 5 minutes to obtain a separator with a conductive layer. At this time, the applicator gap (clearance formed between the separator and the applicator) was 45 μm. The obtained separator was cut into a rectangle, folded in half along the long side so that the conductive layer was on the inside, and both ends of the separator were closed in a direction perpendicular to the folded side to produce a pouch-shaped separator with one side open. The negative electrode was inserted into the pouch-shaped separator. A lead-acid battery was obtained using the substrate, the obtained conductive layer, and the method described in the above section "Unit water reduction amount (liquid reduction characteristic)", and the results of evaluation according to the above evaluation method are shown in Table 1.

[0064] Example 2 The same procedure as in Example 1 was carried out, except for the following points. For the zinc compound dispersion, the amount of zinc oxide (manufactured by Sakai Chemical Industry Co., Ltd. 1) was 40 mass% based on the total mass of the solid content in the slurry, and the amount of the ionic surfactant was 12.0 mass% based on the total mass of the solid content in the slurry. For the slurry, the amount of carbon black was 25.8 mass% based on the total mass of the solid content in the slurry, and the amount of the ionic surfactant was 7.7 mass% based on the total mass of the solid content in the slurry.

[0065] Example 3 The same procedure as in Example 1 was carried out, except for the following points. For the zinc compound dispersion, the amount of zinc oxide (manufactured by Sakai Chemical Industry Co., Ltd. 1) was 5 mass% based on the total mass of the solid content in the slurry, and the amount of the ionic surfactant was 1.5 mass% based on the total mass of the solid content in the slurry. For the slurry, the amount of carbon black was 60.8 mass% based on the total mass of the solid content in the slurry, and the amount of the ionic surfactant was 18.2 mass% based on the total mass of the solid content in the slurry.

[0066] Example 4 The same procedure as in Example 1 was carried out, except for the following points. For the zinc compound dispersion, the amount of zinc oxide (manufactured by Sakai Chemical Industry Co., Ltd. 1) was 60 mass% based on the total mass of the solid content in the slurry, and the amount of the ionic surfactant was 18 mass% based on the total mass of the solid content in the slurry. For the slurry, the amount of carbon black was 5.8 mass% based on the total mass of the solid content in the slurry, and the amount of the ionic surfactant was 1.7 mass% based on the total mass of the solid content in the slurry.

[0067] Example 5 The same procedure as in Example 3 was carried out, except that the metal or metal compound in Example 3 was changed to product 2 manufactured by Sakai Chemical Industry Co., Ltd.

[0068] Example 6 The same procedure as in Example 2 was carried out, except that the metal or metal compound in Example 2 was changed to product 3 manufactured by Sakai Chemical Industry Co., Ltd.

[0069] Example 7 The same procedure as in Example 1 was carried out, except that the metal or metal compound in Example 1 was changed to zinc sulfate (manufactured by Fuji Film Wako Pure Chemical Industries, Ltd.).

[0070] Example 8 The same procedure as in Example 2 was carried out, except that the metal or metal compound in Example 2 was changed to zinc sulfate (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.).

[0071] Example 9 The same procedure as in Example 1 was carried out, except for the following points: For the slurry, 22.9% by mass of carbon black manufactured by Cabot Corporation and 22.9% by mass of carbon black manufactured by Denka Corporation were used based on the total mass of the solids in the slurry, the amount of ionic surfactant was 13.7% by mass based on the total mass of the solids in the slurry, the amount of acrylic copolymer latex was 13.2% by mass based on the total mass of the solids in the slurry, and the amount of thickener (CMC) was 1.3% by mass based on the total mass of the solids in the slurry.

[0072] Example 10 The same procedure as in Example 1 was carried out, except for the following points: For the slurry, the amount of carbon black was 44.6% by mass based on the total mass of the solids in the slurry, 2.5% by mass of a mixture of carbon nanotubes and a thickener (manufactured by Kusumoto Chemicals) was added based on the total mass of the solids in the slurry, the amount of ionic surfactant was 13.7% by mass based on the total mass of the solids in the slurry, and the amount of acrylic copolymer latex was 13.2% by mass based on the total mass of the solids in the slurry.

[0073] Example 11 The same procedure as in Example 1 was carried out, except for the following points: For the slurry, 22.3% by mass of carbon black manufactured by Cabot Corporation and 22.3% by mass of carbon black manufactured by Denka Corporation were used based on the total mass of the solid content in the slurry, 2.5% by mass of a mixture of carbon nanotubes and a thickener manufactured by Kusumoto Chemicals was added based on the total mass of the solid content in the slurry, the amount of ionic surfactant was 13.7% by mass based on the total mass of the solid content in the slurry, and the amount of acrylic copolymer latex was 13.2% by mass based on the total mass of the solid content in the slurry.

[0074] Example 12 The separator obtained in Example 1 was cut into a rectangle and folded in half along its long side so that the conductive layer was on the outside, and the same procedure as in Example 1 was carried out.

[0075] Example 13 The same procedure as in Example 1 was carried out, except that the slurry obtained in Example 1 was manually applied (hand coated) to both sides of the substrate.

[0076] Example 14 The same procedure as in Example 3 was carried out, except that the zinc or zinc compound in Example 3 was replaced with the zinc or zinc compound manufactured by Sakai Chemical Industry Co., Ltd. 3.

[0077] Example 15 The same procedure as in Example 3 was carried out, except that the zinc or zinc compound in Example 3 was changed to Sakai Chemical Industry Co., Ltd. 4.

[0078] Example 16 The same procedure as in Example 1 was carried out, except that the zinc or zinc compound in Example 1 was changed to Sakai Chemical Industry Co., Ltd. 3.

[0079] Example 17 The same procedure as in Example 2 was carried out, except that the zinc or zinc compound in Example 2 was changed to Sakai Chemical Industry Co., Ltd. 4.

[0080] Example 18 The same procedure as in Example 1 was carried out, except that the zinc or zinc compound in Example 1 was changed to Sakai Chemical Industry Co., Ltd. 4.

[0081] Example 19 The same procedure as in Example 1 was carried out, except for the following points. For the zinc compound dispersion, the amount of zinc oxide (manufactured by Sakai Chemical Industry Co., Ltd. 1) was 49.4% by mass based on the total mass of the solid content in the slurry, and the amount of the ionic surfactant was 1% by mass based on the total mass of the solid content in the slurry. For the slurry, the amount of carbon black was 32.9% by mass based on the total mass of the solid content in the slurry, a mixture of carbon nanotubes and a thickener (manufactured by Kusumoto Chemical Industry Co., Ltd.) was added at 0.1% by mass based on the total mass of the solid content in the slurry, the amount of the ionic surfactant was 9.4% by mass based on the total mass of the solid content in the slurry, the amount of the acrylic copolymer latex was 6.6% by mass based on the total mass of the solid content in the slurry, and the amount of the thickener (CMC) was 0.6% by mass based on the total mass of the solid content in the slurry.

[0082] Example 20 The same procedure as in Example 1 was carried out, except for the following points. For the zinc compound dispersion, the amount of zinc oxide (manufactured by Sakai Chemical Industry Co., Ltd. 1) was 39.5% by mass based on the total mass of the solid content in the slurry, and the amount of the ionic surfactant was 1% by mass based on the total mass of the solid content in the slurry. For the slurry, the amount of carbon black was 39.5% by mass based on the total mass of the solid content in the slurry, a mixture of carbon nanotubes and a thickener (manufactured by Kusumoto Chemical Industry Co., Ltd.) was added at 0.3% by mass based on the total mass of the solid content in the slurry, the amount of the ionic surfactant was 11.2% by mass based on the total mass of the solid content in the slurry, the amount of the acrylic copolymer latex was 7.9% by mass based on the total mass of the solid content in the slurry, the amount of the thickener (CMC) was 0.6% by mass based on the total mass of the solid content in the slurry, and the applicator gap was 35 μm.

[0083] Example 21 The same procedure as in Example 1 was carried out, except for the following points. Iron oxide (manufactured by Kojundo Chemical Laboratory Co., Ltd.) was used instead of zinc oxide (manufactured by Sakai Chemical Industry Co., Ltd. 1). The prepared substrate and conductive layer were cut into a rectangle, immersed in dilute sulfuric acid at 25°C for 24 hours, washed with water, air-dried for 24 hours, and dried at 80°C for 5 minutes to be used as a separator, and zinc was dissolved in dilute sulfuric acid with a specific gravity of 1.28 in advance to give a metal equivalent of 0.24 g / L to obtain an electrolyte, to obtain a lead-acid battery.

[0084] Example 22 The same procedure as in Example 2 was carried out, except for the following points. Iron oxide (manufactured by Kojundo Chemical Laboratory Co., Ltd.) was used instead of zinc oxide (manufactured by Sakai Chemical Industry Co., Ltd. 1). The prepared substrate and conductive layer were cut into a rectangle, and then immersed in dilute sulfuric acid at 25°C for 24 hours, washed with water, air-dried for 24 hours, and dried at 80°C for 5 minutes to be used as a separator. As an electrolyte, zinc was dissolved in dilute sulfuric acid with a specific gravity of 1.28 in advance to a concentration of 0.48 g / L in terms of metal, to obtain a lead-acid battery.

[0085] Comparative Example 1 The slurry was carried out in the same manner as in Example 1, except that iron oxide (manufactured by Kojundo Chemical Laboratory Co., Ltd.) was used instead of the zinc oxide (manufactured by Sakai Chemical Industry Co., Ltd. 1) used in Example 1.

[0086] Comparative Example 2 The same procedure as in Example 1 was carried out except for the following points. The zinc compound dispersion liquid was not contained. For the slurry, the amount of carbon black was set to 64.6% by mass based on the total mass of the solid content in the slurry, a mixture of carbon nanotubes and a thickener (manufactured by Kusumoto Chemical Industries) was added at 2.5% by mass based on the total mass of the solid content in the slurry, the amount of ionic surfactant was set to 19.7% by mass based on the total mass of the solid content in the slurry, the amount of acrylic copolymer latex was set to 13.2% by mass based on the total mass of the solid content in the slurry, and the aprotic polar solvent was set to 5% by mass of N-methyl-2-pyrrolidone (NMP) based on the total mass of the slurry.

[0087] Comparative Example 3 The same procedure as in Example 1 was carried out, except for the following points. For the zinc compound dispersion, the amount of zinc oxide (manufactured by Sakai Chemical Industry Co., Ltd. 1) was 64.6% by mass based on the total mass of the solids in the slurry, and the amount of the ionic surfactant was 19.7% by mass based on the total mass of the solids in the slurry. For the slurry, carbon black was not contained, the ionic surfactant was not contained, the amount of the acrylic copolymer latex was 13.2% by mass based on the total mass of the solids in the slurry, and the amount of the thickener (CMC) was 0.6% by mass based on the total mass of the solids in the slurry.

[0088] Comparative Example 4 The same procedure as in Example 21 was carried out, except that dilute sulfuric acid with a specific gravity of 1.28 was used as the electrolyte.

[0089] [Table 1]

[0090] Fig. 1 is an example of an MD-ND cross-sectional image by SEM of a lead-acid battery separator having a conductive layer of Example 1. In Fig. 1, particles that appear darker gray to black than the background are a dispersed phase formed of zinc oxide particles. [Industrial Applicability]

[0091] The lead-acid battery separator of the present disclosure is useful for lead-acid batteries, such as flooded batteries (FB), and is particularly suitable as a separator for enhanced flooded batteries (EFB). [Explanation of symbols]

[0092] 1 Continuous Phase 2 Dispersed phase 2' Dispersed phase 3. Center of gravity of dispersed phase 4 Distance between centers of gravity 5 Dispersed phase bordering the outer frame of the image 10. Image to be analyzed

Claims

1. A separator for a lead-acid battery, comprising a substrate and a conductive layer laminated on at least one surface of the substrate, The conductive layer includes a continuous phase formed of a conductive material, and a dispersed phase in the continuous phase, the dispersed phase being formed of at least one low potential metal material selected from the group consisting of metals having a standard electrode potential of −0.7 V or less, metal compounds containing the metals, and combinations thereof.

2. 2. The lead-acid battery separator according to claim 1, wherein a ratio of an area of ​​the dispersed phase to an area of ​​the continuous phase is 1% or more and 60% or less in a cross-sectional view in an MD-ND cross section of the conductive layer.

3. 3. The separator for a lead acid battery according to claim 1, wherein the low potential metal material comprises zinc or a zinc compound.

4. The separator for a lead acid battery according to any one of claims 1 to 3, wherein the conductive material comprises a carbon material.

5. The separator for a lead-acid battery according to any one of claims 1 to 4, wherein the average closest interphase distance in a cross-sectional view in an MD-ND cross section of the conductive layer is 0.1 µm to 2 µm.

6. The lead acid battery separator according to any one of claims 1 to 5, wherein the maximum diameter of the low potential metal material is 0.1 µm to 15 µm.

7. The separator for a lead acid battery according to any one of claims 1 to 6, wherein the amount of the low potential metal material is 5% by mass to 60% by mass based on the total mass of the conductive layer.

8. The separator for a lead acid battery according to any one of claims 1 to 7, wherein the low potential metal material is at least one selected from the group consisting of zinc oxide and zinc sulfate.

9. A separator for a lead-acid battery described in any one of claims 1 to 8, wherein the conductive material includes a carbon material, and the carbon material is at least one selected from the group consisting of furnace black, acetylene black, ketjen black and carbon nanotubes.

10. A lead-acid battery comprising a positive electrode, a negative electrode, and the separator according to any one of claims 1 to 9 between the positive electrode and the negative electrode.

11. A lead-acid battery comprising a positive electrode, a negative electrode, a separator between the positive electrode and the negative electrode, and an electrolyte, The separator is A substrate and a conductive layer laminated on at least one surface of the substrate, the conductive layer comprises a conductive material, and holes are present in the conductive layer; When viewed in a MD-ND cross section of the conductive layer, a ratio of an area of ​​the holes to an area of ​​the conductive layer is 1% or more and 60% or less; The electrolyte contains at least one low potential metal material selected from the group consisting of a metal having a standard electrode potential of −0.7 V or less, a metal compound containing the metal, and a combination thereof.

12. 12. The lead-acid battery of claim 11, wherein the low potential metallic material is zinc or a zinc compound.

13. 13. The lead acid battery of claim 11 or 12, wherein the conductive material comprises a carbon material.

Citation Information

Patent Citations

  • Lead battery

    JP2013084362A

  • Improved lead-acid battery separator, battery and method of making same

    JP2017515284A

  • Functionalized lead-acid battery separator, improved lead-acid battery, and related methods

    JP2018530125A

  • Improved separator, lead-acid battery, and related methods

    JP2019505969A

  • Improved lead-acid battery separator, battery, and related methods

    JP2020524381A